1995
DOI: 10.1128/jb.177.23.6836-6843.1995
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nuclear genes encoding mitochondrial proteins in Saccharomyces cerevisiae

Abstract: Selection for mutants which release glucose repression of the CYB2 gene was used to identify genes which regulate repression of mitochondrial biogenesis. We have identified two of these as the previously described GRR1/CAT80 and ROX3 genes. Mutations in these genes not only release glucose repression of CYB2 but also generally release respiration of the mutants from glucose repression. In addition, both mutants are partially defective in CYB2 expression when grown on nonfermentable carbon sources, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…amino acids of the C terminus of the 220-amino acid protein (5,21,23). The placement of Med19(Rox3) in this model and its genetic interactions (16,18,19) are more consistent with it being characterized as a Middle module subunit (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…amino acids of the C terminus of the 220-amino acid protein (5,21,23). The placement of Med19(Rox3) in this model and its genetic interactions (16,18,19) are more consistent with it being characterized as a Middle module subunit (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…An additional possibility is that the absence of Med19(Rox3) might also lead to a stabilization of the proposed Head-Tail interaction, even while it destabilizes the interaction of the Middle module with the Head-Tail complex. Med19(Rox3) exerting both stabilizing and destabilizing effects on the complex would be consistent with its dual role in both activation and repression observed in the cell (16,18,19,23,24).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, the yeast Gal11 and Rox3 subunits are required for Gal4 activation of galactose-inducible genes (Suzuki et al 1988;Brown et al 1995), Nut2 for Gcn4-mediated activation of amino acid biosynthetic genes (Han et al 1999), and Med11 for MFa2 transcriptional activation (Han et al 1999). Similar activator-specific functions of individual subunits have been described for Drosophila Mediator, including a role for MED23 in heat-shock gene expression and MED16 in lipopolysaccharide gene expression (Kim et al 2004).…”
mentioning
confidence: 80%
“…Even though the Mediator complex as a whole is required in general for Pol II transcription, some of its subunits function in an activator-specific manner to modulate the expression of a distinct subset of genes (13,15,23). In addition, genetic evidence suggests that a subset of the Mediator proteins are involved in transcriptional repression (4,8,17,35). Differential dissociation of the Mediator components by high-urea treatment (22) and compositional analysis of mutant hpol II complexes (23,24,26) revealed that Mediator subunits with similar genetic properties form distinct modular subassemblies.…”
mentioning
confidence: 99%